2017
DOI: 10.1016/j.eplepsyres.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Defects at the crossroads of GABAergic signaling in generalized genetic epilepsies

Abstract: Seizure disorders are very common and affect 3% of the general population. The recurrent unprovoked seizures that are also called epilepsies are highly diverse as to both underlying genetic basis and clinic presentations. Recent genetic advances and sequencing technologies indicate that many epilepsies previously thought to be without known causes, or idiopathic generalized epilepsies (IGEs), are virtually genetic epilepsy as they are caused by genetic variations. IGEs are estimated to account for ~15-20% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 110 publications
(124 reference statements)
0
31
0
2
Order By: Relevance
“…Emerging research has demonstrated that PRRT2‐related diseases are attributable to synaptopathies . PRRT2 was found to play a key role in presynaptic vesicle secretion, especially for synchronous neurotransmitter release .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging research has demonstrated that PRRT2‐related diseases are attributable to synaptopathies . PRRT2 was found to play a key role in presynaptic vesicle secretion, especially for synchronous neurotransmitter release .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research has demonstrated that PRRT2-related diseases are attributable to synaptopathies. 31,32 PRRT2 was found to play a key role in presynaptic vesicle secretion, especially for synchronous neurotransmitter release. 16 Many genes encoding synaptic proteins, such as STXBP1, 33 SNAP25, 34 and STX1B, 20 have been linked to paroxysmal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the widespread distribution of GABA in cerebral structures, in particular, in areas related to motor function, such as frontal cortex or basal ganglia (e.g., striatum, globus pallidus, subthalamic nucleus and substantia nigra), it can be expected that dysregulation of GABA-ergic neurotransmission, resulting from ischemia, may be responsible for enhancing of disorders, such as paresis, muscular tone dysregulation, or involuntary movements [61]. It can be also responsible for initiation of the epileptic activity [62]. Other brain areas in which GABA-ergic transmission disorders can bring about characteristic dysfunctions are limbic structures, such as hippocampus, amygdala, or prefrontal cortex.…”
Section: γ-Aminobutyric Acidmentioning
confidence: 99%
“…However, its role in GABAergic synapses in pyramidal neurons has not been studied yet. Interestingly, haplodeficiency of the S-SCAM gene is associated with infantile spasms 17 , the most common and severe form of epilepsy in infants and childhood, suggesting the potential pathogenic role of S-SCAM deficiency in GABAergic function 18 . Moreover, S-SCAM transgenic mice showed reduced GABA A receptor α1 levels, specifically in the synaptosomal fraction (biochemical correlates of synapses) without alterations in its total protein levels 13 , indicating the possibility of defects in GABAergic synapses.…”
mentioning
confidence: 99%